Validity of the SF-12 for Use in a Low-Income African American Community-Based Research Initiative (REACH 2010) - Celia O. Larson, PhD; David Schlundt, PhD; Kushal Patel, PhD; Katina Beard, MS; Margaret Hargreaves, PhD (Preventing Chronic Disease, 2008)
IntroductionThe objective of our study was to assess the psychometric properties of the Medical Outcomes Study’s 12-Item Short Form Survey Instrument (SF-12) for use in a low-income African American community. The SF-12, a commonly used functional health status assessment, was developed based on responses of an ethnically homogeneous sample of whites. Our assessment addressed the appropriateness of the instrument for establishing baseline indicators for mental and physical health status as part of Nashville, Tennessee’s, Racial and Ethnic Approaches to Community Health (REACH) 2010 initiative, a community-based participatory research study.MethodsA cross-sectional random residential sample of 1721 African Americans responded to a telephone survey that included the SF-12 survey items and other indicators of mental and physical health status. The SF-12 was assessed by examining item-level characteristics, estimates of scale reliability (internal consistency), and construct validity.ResultsConstruct validity assessed by the method of extreme groups determined that SF-12 summary scores varied for individuals who differed in self-reported medical conditions. Convergent and discriminate validity assessed by multitrait analysis yielded satisfactory coefficients. Concurrent validity was also shown to be satisfactory, assessed by correlating SF-12 summary scores with independent measures of physical and mental health status.ConclusionThe SF-12 appears to be a valid measure for assessing health status of low-income African Americans.